2020
DOI: 10.1002/jgc4.1233
|View full text |Cite
|
Sign up to set email alerts
|

Understanding genetic learning needs of people affected by rare disease

Abstract: Nearly 350 million people worldwide are affected by a rare disease (RD) and ~80% of RDs have a genetic type, underscoring the need for access to reliable genomics education. Patient assistance in resource development can help ensure content is appropriate. The aim of this study was to define the needs and practical usage of the RD community to inform the scope and content of an online genetic course targeted toward the entire RD ecosystem. A high-level online survey (OS) was disseminated to 586 RD patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Disease-related information seeking, and education are widespread RD community needs [42][43][44][45]. The differentiated and unmet information needs of CDG families, their interest in digital innovations, their use of social media and of POs to overcome information-related gaps have been documented and inspired the adopted ImmunoCDGQ engagement strategies [16,41].…”
Section: Discussionmentioning
confidence: 99%
“…Disease-related information seeking, and education are widespread RD community needs [42][43][44][45]. The differentiated and unmet information needs of CDG families, their interest in digital innovations, their use of social media and of POs to overcome information-related gaps have been documented and inspired the adopted ImmunoCDGQ engagement strategies [16,41].…”
Section: Discussionmentioning
confidence: 99%
“…8 A number of studies have explored the specific needs of people with a rare condition. [9][10][11] Access to appropriate specialist services, finding a generalist health provider who is willing to learn about the condition, living with uncertainty of what is best practice, and the trial and error nature of discovering it have all been reported. 4 Electronic resources, by which we mean mobile applications, websites, virtual monitoring devices, social media platforms, telehealth capability and online portals, hold promise of greater connectivity and collaboration in the field of rare diseases.…”
Section: Open Accessmentioning
confidence: 99%
“…A number of studies have explored the specific needs of people with a rare condition 9–11. Access to appropriate specialist services, finding a generalist health provider who is willing to learn about the condition, living with uncertainty of what is best practice, and the trial and error nature of discovering it have all been reported 4…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that people with rare conditions have differing needs from those with high-incidence conditions (eg, [15][16][17]). Although high-prevalence disorders may be no less distressing or onerous to care for, rare diseases have unique features: the lengthy odyssey to find a diagnosis, then to find appropriate specialists who know about the disorder; the lack of evidence about effective treatments, guidelines, or access to knowledgeable general health service providers; and isolation from peer support.…”
Section: Introductionmentioning
confidence: 99%